2001
DOI: 10.1302/0301-620x.83b4.0830561
|View full text |Cite
|
Sign up to set email alerts
|

Localised deposition of amyloid in tears of the rotator cuff

Abstract: A ge-related localised deposition of amyloid in connective tissue has been found in degenerative articular and periarticular tissue. Biopsies of the supraspinatus tendon of 28 patients undergoing repair of the rotator cuff were analysed histologically for the presence of localised deposition of amyloid. There was a long history of impingement in 20 patients, and eight patients had suffered an acute traumatic tear with no preceding symptoms. Localised deposition of amyloid identified by Congo Red staining was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, the failure rate of these repairs is very high, estimated at up to 75 % (Galatz et al, 2004;Bishop et al, 2006;Huijsmans et al, 2007;Sugaya et al, 2007). A number of studies have shown that in late disease stages the tendon itself is extremely degenerate, with reduced cell numbers and poor matrix organisation (Cole et al, 2001;Benson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the failure rate of these repairs is very high, estimated at up to 75 % (Galatz et al, 2004;Bishop et al, 2006;Huijsmans et al, 2007;Sugaya et al, 2007). A number of studies have shown that in late disease stages the tendon itself is extremely degenerate, with reduced cell numbers and poor matrix organisation (Cole et al, 2001;Benson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This reduced suture tissue‐holding strength in degenerative tears is most likely an irreversible structural change. Matthews et al [32] and Cole et al [8] demonstrated the marked degeneration, amyloid deposition and chondroid metaplasia in chronic tears. Additionally, torn and degenerated cuffs are much thinner than intact ones in the area where the sutures are placed.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfated GAG are associated with acute inflammation and new matrix formation, as well as amyloid production. A study conducted by Cole [42] demonstrated that supraspinatus chronic tears were characterized by 70% amyloid deposition on tendon context, unlike only 25% in patients suffering from acute traumatic injuries.…”
Section: Advances In Shoulder Surgerymentioning
confidence: 99%